Diversitas Ekonomi Desa Mayangan Menggunakan Break Even Point sebagai Dasar Perencanaan Laba dalam Membangun Ekonomi Masyarakat: Studi Kasus Pantai Wisata Pondok Bali Kabupaten Subang - Setiawan, Erik; Wanta; Romli, Asep Darojatul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The development of tourism in coastal areas has the potential to have a positive impact on the local community's economy. This study aims to analyze the role of the break even point as a basis for profit planning for economic diversity at Pondok Wisata Bali Beach in Subang Regency. The research method uses a qualitative approach with case studies to gain an in-depth understanding of economic dynamics and their impacts. The research findings reveal that Pondok Wisata Bali Beach has created various economic sectors around it, including hotels, restaurants, handicrafts, as well as local agriculture. This economic diversity has provided new opportunities in terms of income and employment, as well as empowering local communities through training and entrepreneurial opportunities. However, environmental sustainability constraints are also an issue that needs attention. The results of the calculation of the Break Even Point on Pondok Bali Subang tourism show that the income is above the break even point so that this Pondok Bali Subang tour earns profits and is safe from losses. This research provides valuable insights for decision makers and practitioners in developing sustainable tourism in the region. Keywords: Economic Diversity. Profit, Break Even Point